Comparison of Measurement Accuracy between Infrared and Ultrasonic Sensors for Collaborative Robot - Rudianto Rudianto; Kevin Ilham Apriandy; Choirun Nisa (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2026)
This study aims to compare the accuracy of two commonly used distance sensors in robotics systems, namely the ultrasonic sensor HC-SR04 and the infrared sensor Sharp GP2Y0A21YK0F, to support the development of collaborative robots (cobots) that require reliable navigation and object detection. The experiments were conducted in four stages: basic accuracy testing over a distance range of 5–50 cm with 2.5 cm intervals, testing under varying temperature and lighting conditions, accuracy testing on five types of reflective materials (metal, glass, wood, plastic, and fabric), and testing with varying object inclination angles of 0°, 15°, 30°, and 45°. The results indicate that the ultrasonic sensor demonstrates more stable performance and greater tolerance to environmental variations and inclination angles, with a maximum error of approximately 2.5 cm at a 45° angle. In contrast, the infrared sensor provides high accuracy at close ranges but is highly sensitive to lighting conditions and certain reflective materials, with errors reaching 8–10 cm for transparent or light-absorbing surfaces. These findings suggest that the ultrasonic sensor is more suitable for general use in cobots operating in dynamic environments, while the infrared sensor is best applied in controlled scenarios or as a complementary sensor. This research provides a foundation for selecting or combining distance sensors in the development of more accurate and efficient navigation and safety systems for collaborative robots.